World Food Programme uses mobile-based monitoring tools to guide programming in three countries, affecting up to 2.6 m persons - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
ICRAF, with WFP, validated using voice-calls over mobile phones to collect nutrition information from women and mothers. The immediate user of this innovation is the WFP's Vulnerability, Assessment and Mapping Unit who provide technical support across WFP and help monitor and trigger responses. Based on the research and engagement, WFP is piloting the use this innovation in three countries, where they serve 2.6 million beneficiaries, and created a training module based on the innovation for further dissemination and scaling.